2020
DOI: 10.1590/0100-29452020278
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of seeds from full-sib guava families to different substrate temperatures

Abstract: Guava is an important fruit in Brazil and worldwide. However, research has yet to advance on its breeding and seed technology, an essential factor for the development of productive genotypes with germination potential which would support the continuity of breeding programs. In search of a methodology for routine analysis testing of guava seeds under genetic control, this study examined the effect of temperature and substrate on the germination of guava seeds from full-sib families. The experiment was laid out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As for the substrate, the lower first count and final emergence value is due to the fact that the commercial substrate has high porosity; and therefore, the contact surface with seeds and water holding capacity is reduced, which can impair root protrusion (SOUZA et al, 2018), unlike what was observed using substrate containing DRL and/or coarse sand. For germination to occur, seeds need to have adequate contact with the substrate so that they absorb water, and thus start the process of using reserves and synthesizing hormones associated with this process (MAITAN et al, 2020;IBANHES NETO et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…As for the substrate, the lower first count and final emergence value is due to the fact that the commercial substrate has high porosity; and therefore, the contact surface with seeds and water holding capacity is reduced, which can impair root protrusion (SOUZA et al, 2018), unlike what was observed using substrate containing DRL and/or coarse sand. For germination to occur, seeds need to have adequate contact with the substrate so that they absorb water, and thus start the process of using reserves and synthesizing hormones associated with this process (MAITAN et al, 2020;IBANHES NETO et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The germination chambers were set to an alternating temperature of 35-25 °C, with a light/ dark photoperiod of 8 h/16 h, respectively. Assessments were carried out on alternate days until the 28th day, when germination speed index and the percentages of normal seedlings, abnormal seedlings and non-germinated seeds were recorded (Maitan et al, 2020).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The State University of Northern Rio de Janeiro (UENF) has been developing a breeding program with the species P. guajava L. The works have yielded promising results, according to Pessanha et al (2011), Campos et al (2013), Oliveira et al (2013), Campos et al (2016), Quintal et al (2017), Maitan et al (2020), Silva et al (2020), Souza et al (2020), Ambrosio et al (2021), and Silva et al (2021). These good results point to the possibility of obtaining inbred guava families through self-pollination, which will allow the development of varieties (pure lines) as well as the production of hybrids through the exploitation of heterosis.…”
Section: Introductionmentioning
confidence: 99%